Small Mammals as Carriers/Hosts of Leptospira spp. in the Western Amazon Forest - Medeiros, Luciana dos Santos; Braga Domingos, Susan Christina; Azevedo, Maria Isabel Nogueira Di; Peruquetti, Rui Carlos; de Albuquerque, Narianne Ferreira; D'Andrea, Paulo Sérgio; Botelho, André Luis de Moura; Crisóstomo, Charle Ferreira; Vieira, Anahi Souto; Martins, Gabriel; Teixeira, Bernardo Rodrigues; Carvalho-Costa, Filipe Anibal; et al. (Frontiers in Veterinary Science, 2020)
Leptospira is a bacteria that causes leptospirosis, and is transmitted through water, soil or mud that is contaminated by the urine of infected animals. Although it is mainly associated with the urban environment, leptospires also circulate in rural and wild environments. This study aimed to investigate the role of small mammals in leptospirosis epidemiology in the western Amazon, Brazil. In total, 103 animals from 23 species belonging to the orders Didelphimorphia and Rodentia were captured. Blood, kidney, and urine samples were collected and Microscopic Agglutination Test (MAT), lipL32 PCR, secY sequencing and culturing were conducted. MAT was reactive on 1/15 sera, and no bacterial isolate was obtained. PCR yielded 44.7% positive samples from 16 species. Twenty samples were genetically characterized and identified as L. interrogans (n=12), L. noguchii (n=4) and L. santarosai (n=4). No statistical association was found between the prevalence of infection by Leptospira spp. in small mammals within carrier/hosts species, orders, study area and forest strata. Our results indicate a high prevalence of pathogenic Leptospira spp. in several rodent and marsupial species and report the first evidence of Leptospira spp. carrier/hosts in the western Amazon.